Neurological Outcomes after Human Umbilical Cord Patch for In Utero Spina Bifida Repair in a Sheep Model - Papanna, Ramesha; Mann, Lovepreet K.; Snowise, Saul; Morales, Yisel; Prabhu, Sanjay P.; Tseng, Scheffer C. G.; Grill, Raymond; Fletcher, Stephen; Moise, Kenneth J., Jr. (American Journal of Perinatology Reports, 2016)
Objectives The objective of our study was to test the hypothesis that in utero repair of surgically created spina bifida in a sheep model using cryopreserved human umbilical cord (HUC) patch improves neurological outcome.Methods Spina bifida with myelotomy was surgically created in timed pregnant ewes at gestational day (GD) 75. The fetuses were randomly assigned to unrepaired versus HUC and treated at GD 95 and then delivered at GD 140. Neurological evaluation was performed using the Texas Spinal Cord Injury Scale (TSCIS), bladder control using ultrasound, and the hindbrain herniation.Results Three lambs without the spina bifida creation served as controls. There were four lambs with spina bifida: two were unrepaired and two underwent HUC repair. The control lambs had normal function. Both unrepaired lambs had nonhealed skin lesions with leakage of cerebrospinal fluid, a 0/20 TSCIS score, no bladder control, and the hindbrain herniation. In contrast, both HUC lambs had a completely healed skin defect and survived to day 2 of life, a 3/20 and 4/20 TSCIS score (nociception), partial bladder control, and normal hindbrain anatomy.Conclusions Cryopreserved HUC patch appears to improve survival and neurological outcome in this severe form of the ovine model of spina bifida.
Keywords: neural tube defect; umbilical cord; regenerative healing; sheep spina bifida model; spina bifida repair